Contenido y aplicación de los derechos de la naturaleza - René Bedón Garzón (Ius Humani. Jornal do direito, 2016)
The Constitution of the Republic of Ecuador of 2008 has established rights in favor of the nature, including constitutional reserves for its creation. During these years, these rights have been better defined by legislation and jurisprudence, as it is shown in the present investigation. In this way, there have been several constitutional protection actions to enforce these rights and specially for guarantee the right of nature and its integral conservation, the suspension of works had already been stopped temporary before obtain the environmental permits from the government in order to generate environmental impacts. Judges have applied the precautionary principle and activities, have suspended some works, in spite of lack of scientific evidence; and rights have been weighted in order to allow restriction to private property, so that remediation tasks are performed an environmental event is achieved and to guarantee the right of nature restoration.